Secondary Gravity Waves Generated by Breaking Mountain Waves Over Europe. Issue 5 (5th March 2020) - Heale, C. J.; Bossert, K.; Vadas, S. L.; Hoffmann, L.; Dörnbrack, A.; Stober, G.; Snively, J. B.; Jacobi, C.
Abstract: A strong mountain wave, observed over Central Europe on 12 January 2016, is simulated in 2D under two fixed background wind conditions representing opposite tidal phases. The aim of the simulation is to investigate the breaking of the mountain wave and subsequent generation of nonprimary waves in the upper atmosphere. The model results show that the mountain wave first breaks as it approaches a mesospheric critical level creating turbulence on horizontal scales of 8–30 km. These turbulence scales couple directly to horizontal secondary waves scales, but those scales are prevented from reaching the thermosphere by the tidal winds, which act like a filter. Initial secondary waves that can reach the thermosphere range from 60 to 120 km in horizontal scale and are influenced by the scales of the horizontal and vertical forcing associated with wave breaking at mountain wave zonal phase width, and horizontal wavelength scales. Large‐scale nonprimary waves dominate over the whole duration of the simulation with horizontal scales of 107–300 km and periods of 11–22 minutes. The thermosphere winds heavily influence the time‐averaged spatial distribution of wave forcing in the thermosphere, which peaks at 150 km altitude and occurs both westward and eastward of the source in the 2 UT background simulation and primarily eastward of the source in the 7 UT background simulation. The forcing amplitude is ∼ 2 × that of the primary mountain wave breaking and dissipation. This suggests that nonprimary waves play a significant role in gravity waves dynamics and improved understanding of the thermospheric winds is crucial to understanding their forcing distribution. Key Points: Mountain wave breaking in the MLT couples directly to secondary waves Tidal winds act like a filter for secondary wave spectra reaching the thermosphere Nonprimary wave forcing is significant and distribution is governed by thermospheric winds